Saint Lucia. Significant achievements 2018 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2019)
The main activities carried out by the Institute in Saint Lucia during 2018 are identified, with respect to the needs and interests of the country, strengthening issues such as governance, agribusiness and in the use of organic gardens. Likewise, work was done on the inclusion of rural women and youth in agriculture. Finally, the production of cocoa and organic products was supported.